"To Live Lives Worthy of God": Leadership and Spiritual Formation in I Thessalonians 2:1–12. Issue 1 (May 2016) - Åkerlund, Truls
Despite a growing interest in research on spiritual formation, prior studies have not discussed the role of leadership in the formation of Christian character. This article seeks to fill this void by addressing how 1 Thessalonians in general, and 2:1–12 in particular, show Paul's goal and method of leadership for community formation. Written as a letter of friendship to a persecuted church, Paul draws attention to his prior visit in the city as a plumb line for Christian behavior and leadership. As such, the letter contributes to the resocialization of Paul's recent converts, stressing the relationship with himself as well as with each other amidst a hostile environment. The study concludes that Paul's leadership is Christocentric in nature, having modeling, adaptability, and relationships as central components.